The effect of seaweed fertilisation on sulfur isotope ratios (δ34S) and grain size in barley: implications for agronomy and archaeological research - Blanz, Magdalena; Gröcke, Darren R.; Martin, Peter; Church, Mike J. (Frontiers in Environmental Archaeology, 2024)
IntroductionStable sulfur isotope ratios (δ34S) in bone collagen are often employed to study the consumption of marine and freshwater fish, wetland grazing, marine foraging patterns, and the possible geographic origins of food sources. However, a recent small-scale crop experiment showed that biofertilisation with seaweed can elevate δ34S in Celtic beans by ca. 10 ‰. Consumption of this food could erroneously suggest a marine diet and therefore has important implications for the reconstruction of past diets and dietary origins. However, limited research has so far been undertaken on cereals.MethodsTo address this issue, a large-scale field trial was undertaken on the Orkney Islands, whereby bere barley (a Scottish landrace, Hordeum vulgare L.) was biofertilised with seaweed at different dosages (25 t/ha, 50 t/ha), with a mineral NPK fertiliser, and left unfertilised as a control.ResultsThe total barley biomass yield was higher and barley grains were enlarged following all fertilisation treatments compared to the control barley. Barley grain and straw from seaweed-fertilised crops had more elevated δ34S values by around 2–3 ‰ compared to unfertilised plants, while the NPK-fertilised grains and plants had δ34S values 1 ‰ lower.DiscussionThese results confirm previous hypotheses that seaweed fertilisation can elevate cereal δ34S values. The comparatively small δ34S difference between control and seaweed fertilised crops in this field trial is likely due to background elevated δ34S values in the soil (+12.7 ‰), which in turn may be due to long-term exposure to oceanic-influenced rain and sea spray and/or possible historical application of seaweed, or the underlying bedrock composition. The results of this study show that seaweed fertilisation can increase barley grain sizes and δ34S values, and thus should be considered when reconstructing land management and dietary practices in the archaeological record.